INDUSTRY DYNAMICS AND INDUSTRY 4.0 drones for remote sensing applications. - Quattrociocchi, Bernardino; Calabrese, Mario; Iandolo, Francesca; Mercuri, Francesco (College teacher) ([S.l.] : ROUTLEDGE, 2022)
The so-called Fourth Industrial Revolution has prompted companies to adapt to a new business paradigm based on digital interconnection and the ability to respond quickly to the needs of consumers and users. These conditions are closely related to the advent of digital technologies that enable the real-time integration of devices and the control of production systems through technological platforms. Based on this logic, this volume aims to investigate the forms and methods being used by the company at present to confront the new business paradigm, commonly known as Industry 4.0, as well as the impact of new digital technologies on corporate evolutionary dynamics and related business models. More specifically, technological challenges will assess the impact of new technologies on productivity and investment in complementary resources--including human, organizational, and managerial capital--as well as the effects related to the introduction of Internet of Things (IoT)-based production processes. By following this approach, the focus subsequently shifts to drone technology, which is considered by many to be one of the most revolutionary Industry 4.0 technologies. In addition to investigating the history and potential applications of drones, many of which proved to be fundamental during the COVID-19 pandemic, the volume emphasizes the related ethical and social aspects such as the degree of knowledge regarding and the public acceptance of drones. The academic and professional approach of this volume allows it to serve as a guide for professionals, entrepreneurs, and academics with a particular interest in both digital innovation and the drone sector.
Keywords: BUSINESS & ECONOMICS / Economics / General; Technological innovations -- Management; Information technology -- Manangement; Organizational change; Internet of things; Remote sensing